Drug interactions in veterinary practice - Abdullah, Abdul Salam (Persatuan Doktor Veterinar Malaysia, 1985)
The possibility of drug interactions in domestic animals is expected to increase with the influx of drugs onto the market and the increase availability of drug combination products for veterinary use. Drug interactions may lead to unexpected and undesirable effects, toxic or fatal. Prolonged duration of anaesthesia due to inhibition of microsomal biotransformation of barbiturate by chloramphenicol has been reported in dogs and cats following use of methohexital and chloramphenicol. Clonic convulsion and respiratory arrest have also been reported in dogs after the combined administration of phenothiazine and piperazine. Rapid successive injections of oxytetracycline and calcium gluconate have resulted in death of cattle due to the formation of emboli (ea-gel} in the jugular vein. The scarcity of drug interaction information in veterinary literature is not an accurate reflection of the incidence of drug interactions in veterinary practice. The lack of clinical evidence on veterinary drug interactions is more likely due to the difficulty of interpretation of such occurrences in animal patients.